Questioning the measurement of the 'fear of crime'. Findings from a major methodological study - Farrall, Stephen; Bannister, Jon; Ditton, Jason; Gilchrist, Elizabeth (The British journal of criminology, 1997)
Research upon the fear of crime has grown substantially in recent years. From its very inception, this field has relied almost exclusively upon quantitative surveys, which have suggested that the fear of crime is a prevalent social problem. However, doubts about the nature of the instruments used to investigate this phenomenon have cumulatively raised the possibility that the fear of crime has been significantly misrepresented. Dealing with the epistemological, conceptual, operational and technical critiques of quantitative surveys in general and of fear of crime surveys in particular, this article suggests that our understanding of the fear of crime is a product of the way it has been researched rather than the way it is. As the aim of the research project under which this data was collected was to develop and design new quantitative questions, the article ends with some possible solutions to the epistemological, conceptual, operational and technical problems discussed which may improve future quantitative research in this field